Prebiotic Supplementation During Gestation Induces a Tolerogenic Environment and a Protective Microbiota in Offspring Mitigating Food Allergy - Selle, Amandine; Brosseau, Carole; Dijk, Wieneke; Duval, Angéline; Bouchaud, Grégory; Rousseaux, Anais; Bruneau, Aurélia; Cherbuy, Claire; Mariadassou, Mahendra; Cariou, Véronique; Barbarot, Sebastien; Bodinier, Marie (Frontiers in Immunology, 2022)
Food allergies are associated with alterations in the gut microbiota, epithelial barrier and immune tolerance. These dysfunctions may observed within the first months of life, revealing that early intervention is crucial for disease prevention. In this context, nutritional strategies involving prebiotics are attractive. Indeed, some prebiotics such as galacto-oligosaccharides and inulin can promote tolerance, epithelial barrier reinforcement and gut microbiota modulation, but the ideal period for intervention is unknown. Herein, in BALB/cJRj mice we investigated whether galacto-oligosaccharides/inulin supplementation during gestation could protect offspring against wheat allergies. We demonstrated that prebiotic supplementation induced a strong restructuration of the fecal microbiota of dams toward beneficial strains during gestation and partially during mid-lactation. This specific microbiota was transferred to pups and maintained to adulthood. Moreover, the rate of B and T regulatory subsets was increased in the lymph nodes of offspring born from supplemented mothers, inducing a tolerogenic environment and protecting them against wheat allergy symptoms. Our study demonstrates that prebiotic supplementation during pregnancy induces, in the offspring, a tolerogenic environment and a microbial imprint leading to the prevention of food allergy development.